Oracle SOA suite 11g handbook - Jellema, Lucas (New York McGraw-Hill, 2011)
"Design and implement an agile service-oriented enterprise computing infrastructure using the detailed information in this Oracle Press guide. Written by an Oracle ACE director, Oracle SOA Suite 11g Handbook uses a hands-on case study to illustrate each programming, management, and governance concept. Get expert techniques for modeling complex business processes and deploying and securing Web services, while maximizing decoupling and code reuse. - Install Oracle SOA Suite 11g or migrate from a previous version - Develop reusable application components using SCA and SDO - Model processes using BPEL, BPMN, and human task components - Establish dynamic routing and logging rules with Oracle Mediator - Apply the principles of Oracle Event-Driven Architecture Suite through Oracle Complex Event Processing, the Event Delivery Network, and the BAM Server - Benefit from the power of Java through the Spring component and the interaction with Oracle Application Development Framework - Transpose and validate heterogeneous data using the Oracle Service Bus - Design, test, and deploy composite applications from the Oracle Fusion Middleware Control Console "--
Includes index
1 2
Keywords: Oracle (Computer file); Service-oriented architecture (Computer science)